NiS1.97: a new efficient water oxidation catalyst for photoelectrochemical hydrogen generation - Bhosale, Reshma; Kelkar, Sarika A.; Parte, Golu; Fernandes, Rohan; Kothari, Dushyant; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2015)
NiS1.97, a sulfur-deficient dichalcogenide, in nanoscale form, is shown to be a unique and efficient photoelectrochemical (PEC) catalyst for H-2 generation by water splitting. Phase pure NiS1.97 nanomaterial is obtained by converting nickel oxide into sulfide by controlled sulfurization method, which is otherwise difficult to establish. The defect states (sulfur vacancies) in this material increase the carrier density and in turn lead to favorable band line-up with respect to redox potential of water, rendering it to be an effective photoelectrochemical catalyst. The material exhibits a remarkable PEC performance of 1.25 mA/cm(2) vs NHE at 0.68 V in neutral pH, which is almost 1000 times superior as compared with that of the stoichiometric phase of NiS2. The latter is well-known to be a cocatalyst but not as a primary PEC catalyst.
Keywords: dichlacogenide; Faradaic efficiency; Hydrogen generation; NiS1.97; nonstoichiometric; photoelectrochemical catalyst; sulfurization